KEMISKINAN MULTIDIMENSI DAN PERLINDUNGAN SOSIAL - Abdul Khaliq; Betty Uspri (Universitas Bunda Mulia, 2017)
This research examines the important issues of multidimensional poverty and social protection. Utilizing the raw data set of Survei Sosial Ekonomi Nasional (SUSENAS) 2014, the empirical findings are estimated by Structural Equation Modelling Bootstrap Aggregating (SEM BAGGING). The method of Structural Equation Modelling Bootstrap Aggregating (SEM BAGGING) is a statistical technique that estimates the pattern of relationship between latent variables and indicators using bootstrap resampling to get a small bias from an original estimation. The estimation results found a statictically negative significant between education, health and quality of lives and multidimensional poverty. Moreover, empirical evidence shows a statistically positive effect multidimensional poverty on social protection in Indonesia. These results are robust across different estimation methods and different level of bootstrap resampling.Keywords : Multidimensional Poverty, Social Protection, SEM BAGGING